Linguistic peculiarities of image-bearing lexical stylistic devices in English and Uzbek fictional works - D.Sh.Tirkashev (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Image-bearing stylistic device are considered language means which serves as figurative language in fictional works. They are used to enable to the reader to imagine the events, characters and settings as the author wishes. Examples of this type of language devices can be found in English and Uzbek literature.